Comparative benchmarking in the light industry in Ukraine - Olena Abramova (Cхід, 2013)
The article deals with the development of comparative benchmarking in the light industry in the manufacture of personal protective equipment. The author developed a method of benchmarking in the sphere of production of personal protective equipment for the purpose of practical application of MB to achieve cost leadership